Epidemiological trends and future projections of ischemic stroke in children and adolescents: a global analysis from 1990 to 2021 - Liu, Yi; Hu, Jianhua; Zhu, Xiaofen (Frontiers in Neurology, 2025)
BackgroundIschemic stroke in children and adolescents is a significant public health concern. This study aims to describe the epidemiological characteristics of ischemic stroke in children and adolescents from 1990 to 2021.MethodsData on ischemic stroke in children and adolescents from 1990 to 2021 were taken from the 2021 Global Burden of Disease (GBD) study. The annual percentage change (AAPC) was used to assess trends in disease burden by region, age, and gender. To examine regional disparities, the Slope Index of Inequality (SII) and Concentration Index (ConcI) were applied. Additionally, the Bayesian Age-Period-Cohort (BAPC) model was employed to predict the disease burden for the next 15 years.ResultsFrom 1990 to 2021, ischemic stroke in children and adolescents increased globally in incidence and prevalence, while mortality and disability-adjusted life years (DALYs) decreased. The disease burden is higher in low-income countries, with females having higher incidence rates and males bearing a greater burden in mortality and DALYs. Environmental factors like high temperatures are linked to increased risk. By 2036, incidence and prevalence may rise, particularly in the 15–19 age group, although mortality and DALYs are expected to continue decreasing.ConclusionIschemic stroke in this group shows an “increasing case number but decreasing mortality” trend, highlighting medical progress but ongoing risks. Challenges include gender differences, regional inequalities, and environmental risks. Targeted prevention strategies are needed to reduce the global disease burden.